Fatores que afetam o suporte fornecido pela medição de desempenho ao processo de melhoria contínua em empresas certificadas ISO 9001. - Miranda, Raissa Alvares de Matos (2005)
The aim of this dissertation was to investigate empirically which factors are affecting the support given by the performance measurement to the continuous improvement process within ISO 9001 registered companies. The continuous improvement is a simple concept that is attracting the attention of several companies around the world, but the results are not always the expected ones. Most of the flaws are due to the lack of appropriate infrastructure, behaviors and practices related to the stages in the evolution of continuous improvement. Among the elements of this infrastructure is the performance measurement that plays an important role in supporting the improvement activities. The performance measurement, though, needs to present an appropriate structure for each stage in the evolution of continuous improvement. The procedure used to develop the field research was the case study to allow the researcher to understand several aspects raised by the research question, by using interview and field observation. Four ISO 9001 registered companies were studied, since the standard requires the execution of performance measurement and continuous improvement. Each company had different experiences according to the quality management. The results of this research proved that the structure of performance measurement is an important key to support the continuous improvement process and that in each stage in the evolution of continuous improvement it has to be different. However, the existence of only an appropriate performance measurement system is not enough. The use of this performance measurement system is between this relation and it is also affected by the knowledge of the organization members to use the performance measurement in the continuous improvement activity.